Optimizing Energy Consumption for Cloud Internet of Things - Ahmed, Zeinab E.; Hasan, Mohammad Kamrul; Saeed, Rashid A.; Hassan, Rosilah; Islam, Shayla; Mokhtar, Rania A.; Khan, Sheroz; Akhtaruzzaman, Md (Frontiers in Physics, 2020)
Internet of Things (IoT) and Cloud Computing (CC) are considered as two of the greatest technology revolutions in the last few years. New technology raised in recent years is known as CloudIoT or Cloud of Things (CoT), which integrates cloud computing and internet of things. Dynamic and heterogeneous environment, energy efficiency, and delay-sensitive are the major issues in CoT. Energy efficiency is one of the basic requirement of IoT applications and resources in cloud, which is really challenging issue in CoT. This paper proposes optimization of energy scheme for CoT by applying genetic algorithm (GA). An extensive numerical simulation is carried out to verify the effectiveness of the proposed method compared to the ETCORA algorithm. The analytical results present better performances of the proposed optimizing energy consumption technique. Results also show that the proposed method indeed outperforms the ETCORA in reducing energy consumption of task requests.